Evaluation of dacryocystorhinostomy using optical coherence tomography and rebamipide ophthalmic suspension - Fujimoto M (Dove Medical Press, 2014)
Masahiro Fujimoto,1 Ken Ogino,1 Chika Miyazaki,1,2 Miou Hirose,1,3 Hiroko Matsuyama,1,4 Takeshi Moritera,1,5 Nagahisa Yoshimura1 1Department of Ophthalmology and Visual Sciences, Kyoto University Graduate School of Medicine, Kyoto, Japan; 2Department of Ophthalmology, Hyogo Prefectural Tsukaguchi Hospital, Hyogo, Japan; 3Department of Ophthalmology, Hyogo Prefectural Amagasaki Hospital, Hyogo, Japan; 4Department of Ophthalmology, National Hospital Organization Himeji Medical Center, Hyogo, Japan; 5Moritera Eye Clinic, Shiga, Japan Purpose: To evaluate the surgical outcome of dacryocystorhinostomy (DCR) by measuring the tear meniscus, using optical coherence tomography and rebamipide ophthalmic suspension. Methods: Patients with nasolacrimal obstruction and chronic dacryocystitis who were scheduled for an endonasal DCR underwent tear meniscus examinations before and 2 months after surgery. Vertical scans of the inferior menisci were performed before and at 1, 3, 5, 7, and 10 minutes after the instillation of rebamipide ophthalmic suspension. The tear menisci areas were measured with imaging software. Ten young adults without epiphora formed the control group.Results: Anatomical success was achieved on 22 sides of 21 patients. The patients’ postoperative tear menisci were significantly smaller than the preoperative menisci at all points during the test, and the response to volume loading in the postoperative patients was corrected to nearly that of the young, healthy adults. Nevertheless, the postoperative meniscus area tended to be larger than that of the young adults at all points.Conclusion: The reduced tear meniscus area after DCR reflected the success of the surgical procedure. However, incomplete recovery of the meniscus after the test might suggest a residual disorder of the lacrimal drainage system after DCR. Keywords: dacryocystorhinostomy, tear meniscus, rebamipide, optical coherence tomography